Terms of early and late prosthetic valve endocarditis - A. A. Krikunov; A. B. Koltunova; S. P. Spysarenko; T. A. Malysheva (Ukrainian Journal of Cardiovascular Surgery, 2018)
Prosthetic valve endocarditis (PVE) is one of the severe complications of the postoperative period from the side of implanted artificial heart valves. Early PVE is associated with mortality rate over 75%.Objectives: to investigate the terms early and lateprosthetic valve endocarditis.Materials and methods. The basis of the study was the clinical data of 276 patients withPVE, who underwent examination and treatment at the SE «AmosovNational Institute of Cardiovascular Surgery AMS of Ukraine». The average age was 42.1±1.1 y. (8.0–73.0 yy.).Results. Depending on the appearance of the first symptoms ofPVE, the group of patients was subdivided into early (less than 2 months after surgery) and late (more than 2 months after surgery)PVE, which included 109 (39.5%) and 167 (60.5%) cases respectively. By the end of the second month, the risk of PVE was 6%, and by the end of the first year after surgery, it was almost halved by 4%.Conclusions. Distribution of occurrence of PVE in the postoperative period was unequal. The greatest number of cases occur on the fourth week after implantation of an artificial heart valve.